Fertilización de pasturas de alfalfa en suelos de la región semiárida pampeana - Fernandez, Romina; Alvarez, Cristian; Sacks, Matias; Quiroga, Alberto Raul (Asociación Argentina de la Ciencia del Suelo, 2023)
Poster